SOSIALISASI LANDASAN PENDIDIKAN DI SEKOLAH DASAR PADA KURIKULUM MERDEKA DI MI MUHAMMADIYAH 16 KARANGASEM - Mudayan, Arfian; MZ, A.F. Suryaning Ati; Putri, Rossa Selfi Yuliana; Sururi, Hamam Afif (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2024)
The socialization of educational foundations within the Merdeka Curriculum in primary schools is crucial for enhancing teachers' understanding as implementers of the new curriculum. This community service aims to introduce the educational foundations that underpin the Merdeka Curriculum to teachers at MI Muhammadiyah 16 Karangasem. The methods employed include lectures, visual presentations, discussions, question-and-answer sessions, and case studies. The results indicate an improvement in teachers' understanding, enthusiasm, and active participation in comprehending the philosophical, juridical, sociological, psychological, and technological foundations of the Merdeka Curriculum. Overall, this activity successfully enhances teachers' understanding of the Merdeka Curriculum's foundations. However, further accompanying programs and ongoing monitoring are necessary to ensure optimal implementation in the field.